Accelerating Parkinson’s Disease drug development with federated learning approaches - Amit Khanna; Jamie Adams; Chrystalina Antoniades; Bastiaan R. Bloem; Camille Carroll; Jesse Cedarbaum; Joshua Cosman; David T. Dexter; Marissa F. Dockendorf; Jeremy Edgerton; Laura Gaetano; Erkuden Goikoetxea; et al. (npj Parkinson's Disease)
Abstract Parkinson’s Disease is a progressive neurodegenerative disorder afflicting almost 12 million people. Increased understanding of its complex and heterogenous disease pathology, etiology and symptom manifestations has resulted in the need to design, capture and interrogate substantial clinical datasets. Herein we advocate how advances in the deployment of artificial intelligence models for Federated Data Analysis and Federated Learning can help spearhead coordinated and sustainable approaches to address this grand challenge.